Community Genetics: a new discipline and its application in Brazil - Antonio Sérgio Ramalho; Roberto Benedito de Paiva e Silva
Community genetics is a new discipline which aims to provide genetic services to the community as a whole. As a science, community genetics encompasses all research needed to develop and evaluate its application. There is no question that the development of community genetics is necessary in Brazil. The implementation of such programs in our country, especially for hemoglobinopathies, has been recommended by the World Health Organization and other international organizations. Apart from the need for and appeal of community genetics programs, some aspects require serious review. This article discusses various cultural, social, psychological, and economic factors that can make genetic screening an invasion of individual privacy